PROFIL KOMUNIKASI MATEMATIS SISWA LAKI-LAKI DAN PEREMPUAN PADA MATERI GEOMETRI BIDANG DATAR DI GUGUS II KECAMATAN MAJALAYA - Yekti Bella Pertiwi; Rayi Siti Fitriani; Wina Mustikaati (STKIP Subang, 2026)
Mathematical communication ability is a crucial skill for elementary school students, enabling them to express mathematical ideas through writing, drawings, and symbols. However, in practice, this ability remains low; for instance, midterm exam results at a school in Karawang Regency fell far short of the ideal score. This study aimed to examine the mathematical communication ability profile of fifth-grade elementary school students in Gugus II Kecamatan Majalaya and to compare the performance of male and female students in solving mathematical communication tasks related to plane geometry. A quantitative descriptive research design was employed, involving 78 fifth-grade students (41 boys and 37 girls). Data were collected using a descriptive test designed to measure mathematical communication skills across three aspects—written text, drawings, and mathematical expressions—after the instrument had undergone testing for validity, reliability, discriminating power, and difficulty level. Data analysis involved descriptive statistics, specifically calculating the mean achievement scores based on a holistic scoring rubric. The results showed that male students achieved a higher average score (11.93) on the third measured indicator compared to female students (10.05). Nevertheless, both groups performed well below the study's ideal average score of 40 Keywords: gender, geometry, mathematical communication, primary school